Entrepreneurial Intention of Engineering Students in Malaysian Polytechnics Institutions: A Theory of Planned Behavior Approached - Rozita, Mokhtar; Yuserrie, Zainuddin (Universiti Malaysia Pahang, 2012)
The issue on unemployment graduates is a serious issue in this era of globalization. To address this problem and in line with the goals of Vision 2020, entrepreneurship is one area that is given special attention by the Malaysian government in employment creation. In accordance with government’s seriousness in developing potential entrepreneurs as building blocks for a more resilient economy, undertaking this study is deem timely in order to identify the level of entrepreneurial intentions among students. Thus, the study was conducted to determine whether the final year diploma students in the area of engineering at the Malaysian Polytechnic Institutions have the intention to become entrepreneur upon graduation. Therefore, this study proposed the entrepreneurial intention among students can be explained by Ajzen’s (1991) Theory of Planned Behavior. This study also trying to investigate the role of attitudinal factors such as attitudes, subjective norms and perceived behavioral control, mediate the relationship between psychological characteristics and entrepreneurial intention. For the purpose of this study, survey method was employed and 217 questionnaires were used in the statistical analyses. Based on regression analysis it was found that the hypothesized linkage between psychological characteristics and entrepreneurial intention was fully supported, while, the role of attitudinal factors mediate the relationship between psychological characteristics and entrepreneurial intention was partially supported. Implications and limitations of the findings are specified. Finally, the findings of this study are suggested for future study.